Management of respiratory motion for lung radiotherapy: a review - Abdul Ghani, Muhammad Nur Hidayat; Ng, Wee Loon (Journal of Xiangya Medicine; Vol 3 (July 2018): Journal of Xiangya Medicine, 2018)
In this review, various motion management techniques in lung radiotherapy treatment are discussed. Accounting for motion or reducing residual motion is crucial in facilitating dose escalation while reducing toxicity to critical organs near the target volume. The motion management techniques in this review are grouped into three main components: imaging, free breathing and breath hold. The importance of respiratory correlated imaging also known as 4 dimensional imaging, is emphasized in this review as it provides a more accurate representation of tumor motion and its acquisition challenges are reviewed in detail. Tumor delineation and consequently the planning target margins rely greatly on the quality and accuracy of image acquisition. Other factors such as reproducibility, patient selection, patient compliance, tumor location should also be considered when choosing the technique to be used. There is no one solution fits all or the ‘best’ technique when managing motion. The different techniques in delivering radiation while accounting for motion are also discussed, with the advantages and limitations of each of these techniques presented objectively.